TOMBSTONES ON CHILDREN BURIALS OF THE 14TH – 15TH CENTURY FROM THE VILLAGE OF KUBACHI: FEATURES OF DECORATIVE FINISH - Mammaev, Misrihan Mamaevic (History, Archeology and Ethnography of the Caucasus, 2019)
The article overviews the grave monuments of the 14th – 15th centuries on children’s burials identified by the author in the 80s of the 20th century in the medieval Muslim cemeteries "Bidakh Khuppe" (in Kubach. - "graves on the other side") and "Tsitsila". These cemeteries are located approximately 1.5-2 km south of the old part of Kubachi, on a lower section of the slope Tsitsila, facing its northern side to the village. A relatively small number of carved gravestones of the 14-15th cc. of these cemeteries has been studied by the author and other researchers. A lot of decorated monuments, including stelas on the graves of children’s burials, remain unexplored. The present paper considers the stelas in comparative terms with synchronously decorated tombstones of burials of adults or old people, the features of their decoration are clarified. It is noted that the small stelas were placed on the children’s graves at the head side, trimmed with floral ornaments. Relief Arabic inscriptions, written in monumental “blooming Kufic” script on a floral ornament background have not been identified on the tombstones under review. In addition to their size, this is one peculiar feature of the steles of children’s burials, which di from the decor of the burial monuments of adults or old people. The reason for it seems to be the fact that it was impossible to place long inscriptions accommodated for large tombstones on smaller slabs; the commonly used inscriptions were, for instance, the epitaph-shahada “There is no god but God, and Muhammad is the messenger of God”, or a saying “Death is the bowl from which everyone drinks; grave is the gate, and everyone enters it” written in large relief letters. In their forms, the tombstones of children’s burials are similar to the ones of burials of adults or old people in rural communities. Of the ten described monuments from the village of Kubachi, only four have proper names of the buried written on them. Tombstones are finished at a rather high artistic level, usually with large relief ornaments in relation to the size of the monument. This can also be attributed to one of the differences between stelas of children’s burials from the stelas of burials of elderly or old people.